(untitled) (Journal of Bangladesh Institute of Planners, 2015)
Water related natural hazards and climate change issues such as flood has become a serious threat to the lives, livelihoods and sustainable development of Bangladesh. Chilmari Upazila of Kurigram district which is one of the most seriously flood affected areas of Bangladesh has been taken as the study area. Bangladesh is already known as a role model for flood risk management around the world. But, the situation of flood management is not the same all around the country. The objectives of this study are to find out the main problems of the flood control and risk management system of Chilmari Upazila, and to develop a planning intervention guideline for its flood control and risk management. The interactive approach of the study involves participation of the stakeholders to develop local solutions to the flood problems. The empirical part of this study is conducted by household questionnaire survey and semi-structured in-depth interviews with questions regarding flood control and risk management. Main findings of the study state that the floods in Chilmari are managed in ad hoc manner. A coordinated and comprehensive management approach along with strong institutional framework is very important for sustainable flood control and risk management at Chilmari. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 111-121